Enhancing digital competence and entrepreneurial orientation in vocational education: Innovations for SMEs in West Java's fashion industry - Asti Nur Aryanti; Suryana Suryana; Heny Hendrayati; Chairul Furqon; Hari Mulyadi; Christianingrum Christianingrum; Palupi Permata Rahmi; Shintia Permata; Jumadil Saputra (Jurnal Pendidikan Vokasi, 2024)
The creative economy is vital for Indonesia's economic growth, especially during a global slowdown. It boosts employment and export values, with culinary, crafts, and fashion leading the way. In 2022, fashion, culinary, and crafts had the highest export values. West  Java is a standout province in this industry. The UMKM Juara program aims to expand markets and digitalize MSMEs. Technology and digital tools are reshaping the business landscape, and the creative industry must embrace these advancements to succeed financially. The purpose of this study was to investigate the effect of digital innovation on business success as a mediator between digital entrepreneurship competence and digital entrepreneurship orientation. The methodology employed was descriptive verification with a quantitative approach. Data were collected using questionnaires. The sampling technique employed was non-probability sampling with purposive sampling, yielding a sample of 306 West Java UMKM Juara in the Fashion Subsector. SEM-AMOS was used to analyze the data in this research. The research findings revealed that digital entrepreneurship competence had a direct and positive effect on business success. Likewise, digital entrepreneurship orientation had a positive effect on business success. Digital innovation mediated digital entrepreneurship competence towards business success. However, digital innovation did not mediate digital entrepreneurship orientation on Business Success.  This findings can be used to improve vocational education curricula or strengthen training programs related to developing digital competencies among learners.